Pengaruh Kepemilikan Institusional, Kepemilikan Terkonsentrasi, Loan to Deposit Ratio, Non Performing Loan, dan Debt to Equity Ratio Terhadap Kinerja Perbankan yang Terdaftar pada Bursa Efek Indonesia Periode 2014-2018 - Kenny Halim Saputra; Diyan Lestari (UNIVERSITAS KALBIS, 2022)
This study seeks to examine the impact of institutional ownership, concentrated ownership, loan-to-deposit ratio, non-performing loans, and debt-to-equity ratio on the performance of Indonesia Stock Exchange-listed banks from 2014 to 2018. Using a technique called purposive sampling, 26 of the 44 banks listed on the IDX fit the criteria. Using the combined regression technique and the EViews 9 software, the data were evaluated. According to the findings of this study, institutional ownership, concentrated ownership, LDR, and NPL have no impact on banking performance, and DER has no impact on banking performance.